B. IS & MIS Information Systems and Management Information Systems: The backbone, sustenance and accomplishment of modern business - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
Information System (IS) has always been mixed up and confused with Management Information System (MIS) by many Information Technology professionals, and even in definitions ascribed to them thereby puzzling many users of Information Technology (IT). It should however, be noted that IS deals with the generality of the process of generating information from data; and MIS is definite about information generation for the use of management to enable them to efficiently / effectively plan, organize, direct, control and govern organisations. Any organisation lacking good IS and MIS for effective management of its functions / activities would be seriously handicapped, and as such could be doomed for collapse. Many modern organisations may be culprits of possessing the needed information for effective management of their enterprise, thereby denying the establishment of achieving its goals. It is a fact that achievement of organisational goals are synonymous with success of the enterprise, and management is required to attain the goals established with the directors of the company.